First observation and branching fraction measurement of the Λ 0 b → D − s p decay - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (Journal of high energy physics, 2023)
Abstract: The first observation of the Λ0b → D−s p decay is presented using proton-proton collision data collected by the LHCb experiment at a centre-of-mass energy of √s = 13 TeV, corresponding to a total integrated luminosity of 6 fb−1.